Словозміна іменників середнього роду, оформлених за зразком субстантивів давніх *-ŏ-, *-jŏ-основ, у західнополіських і суміжних говірках - Зінчук, Руслана; Zinchuk, Ruslana (Східноєвропейський національний університет імені Лесі Українки, 2016)
На матеріалі західнополіських і суміжних говірок проаналізо¬вано словозміну іменників середнього роду, оформлених за зразком субстантивів давніх *-ǒ-, *-jǒ-основ. З’ясовано чинники впливу на існування діалектних відмінностей у досліджуваній формотвірній системі. Встановлено, що специфіку діалектної парадигми аналізованих іменників визначають інтенсивні процеси інноваційного характеру, зокрема типові для говірок фонетичні закономірності та граматична аналогія. Вказано на продуктивність фонетично видозмінених давніх флексій субстантивів колишніх *-ǒ-, *-jǒ-основ. The article highlights the peculiarities of inflection of neuter gender nouns formed on the model of the old substantives with *-ǒ-, *-jǒ-stems. The emphasis is laid on the factors affecting the existence of dialect differences in the inflectional system under the analysis. The author argues the specifics of dialectal paradigm of the analyzed nouns and concludes that they are determined by the intensive processes of innovative character, including phonetic patterns typical for dialects and grammatical analogy. The study singles out the productivity of the phonetically modified old former inflections of the substantives with *-ǒ-,*-jǒ-stems. The remains of doubling plural forms of neuter nouns in the nominative and the accusative cases are interpreted as expressive/emphatic morphological archaisms. The illustrative examples of variant actualization of every specific ending in one dialect clearly testify that the process of establishing inflectional dialect standards is still in progress.
Inflexions of Neuter Nouns Formed According to the Model of Old Substantives with *-ǒ-, *-jǒ-stems in Western Polissian and Related Dialects.
Keywords: говірка; словозміна; іменник; відмінок; флексія; граматична аналогія; фонетична інновація; patois; form inflections; noun; case; flexion; grammatical analogy; phonetic innovation